Thermo-catalytic Degradation of Thermocol Waste to Value Added Liquid Products - K. Panda, Achyut; Singh, R.K.; Mishra, D.K. (Asian Journal of Chemistry, 2012)
Kaolin clay and amorphous silica alumina have been studied as catalysts in the degradation of waste thermocol (expanded polystyrene) in a stainless steel autoclave surrounded by a furnace at different temperatures ranging from 350-550 ºC under partial oxidation condition. The major fraction of the pyrolysis reaction is an oily liquid, which is highly volatile. In the pyrolysis optimization studies, the highest yield of liquid product obtained is 93 % in thermal and 94.5 % in presence of kaolin at 500 ºC with 1:10 catalyst to plastic ratio. Although there is no considerable change in kinetics and yield of liquid products in the degradation reaction using the catalysts but they altered the product distribution. In thermal pyrolysis the amount of styrene is 78 %, which decreased in presence of both the catalysts and out of the two catalysts tested silica-alumina show the highest yield of ethyl benzene and the lowest of styrene.